T-Cell Repertoire Characteristics of Asymptomatic and Re-Detectable Positive COVID-19 Patients - Li, Yizhe; Hu, Jian; Wang, Yongsi; Liu, Dongdong; Shi, Yaling; Zhang, Jiaqi; Liu, Yuntao; Lin, Dongzi; Lin, Jing; Hu, Wei; He, Haolan; Wang, Wei; et al. (Frontiers in Immunology, 2022)
The prevention of COVID-19 pandemic is highly complicated by the prevalence of asymptomatic and recurrent infection. Many previous immunological studies have focused on symptomatic and convalescent patients, while the immune responses in asymptomatic patients and re-detectable positive cases remain unclear. Here we comprehensively analyzed the peripheral T-cell receptor (TCR) repertoire of 54 COVID-19 patients in different courses, including asymptomatic, symptomatic, convalescent and re-detectable positive cases. We identified a set of V-J gene combinations characterizing the upward immune responses through asymptomatic and symptomatic courses. Furthermore, some of these V-J combinations could be awakened in the re-detectable positive cases, which may help predict the risk of recurrent infection. Therefore, TCR repertoire examination has the potential to strengthen the clinical surveillance and the immunotherapy development for COVID-19.